Impact of geochemical reactivity on desulphation requirements in a sandstone reservoir containing carbonate and sulphate minerals - Al-Behadili, Ali M.; Mackay, Eric J. (Frontiers in Chemistry, 2025)
This paper presents an investigation of the impact of in situ chemical and geochemical interactions on oil recovery efficiency and inorganic scale management. A common technique to support the reservoir pressure is water injection, but scale problems can be a major issue that develop during oil field production when there is water (especially seawater) injection. In such flooding scenarios, geochemical reactions occur between formation and injected water in terms of sulphate scales, such as barite. On the other hand, the carbonate scales may form due to a variety of reasons: changes in temperature, pressure, pH and CO2 concentration in the aqueous or hydrocarbon phases. This paper investigates the impact of CO2 availability, and changes in pH, ionic concentrations and temperature on carbonate and sulphate scaling risk in waterflooded reservoirs where choices may be exerted over injection water composition. In this work, the injected water does not contain CO2, but CO2 is present in the oil phase, and may partition from there, or diffuse from the formation water. Also presented is the relationship between brine composition and scale precipitation and management in the production wells. There are various factors affecting the system, such as water injection well and production well flow rates and flow through the reservoir, and also compositional effects due to use of Full Sulphate Seawater (FSSW) or Low Sulphate Seawater (LSSW), and due to variations in temperature and the concentration of CO2 in the oil phase. In this study, as preparation for addition of geochemistry to a full field 3D history matched model, we include geochemical reactions in a 1D model that has the field pressure, temperature and fluid properties, to test the impact of the various potential reactions in a simple system. This is necessary to fully understand the system before, in future work, moving on to the full field modelling, and in fact provides very valuable learnings that would be more difficult to distil if full field modelling alone had been performed. We assume the mineral reactions (anhydrite, gypsum, barite, huntite and calcite) are in equilibrium, excepting for the magnesium rich carbonate mineral reaction, which is assumed to be kinetic. The results shows that SO42-, Mg2+, HCO3− and Ca2+ are the major ions that have a very significant effect on the system, and therefore impact on precipitation (4.7E-06gmole) and dissolution (-4E-06gmole) of calcite, barite and the magnesium rich carbonate mineral. Dissolution of anhydrite (−5.1E-05gmole) present in the initial mineral assemblage is shown to have a significant impact in most scenarios, except where FSSW has been heated up to reservoir temperature, where anhydrite precipitation (5E-05gmole) in situ occurs. This has a significant impact on the levels of desulphation that should be used to prevent sulphate scales in the production wells.